Co-liquefaction behavior of corn straw and Shengli lignite. Issue 3 (August 2016) - Li, Liang; You, Quan; Wu, Shiyong; Huang, Sheng; Wu, Youqing; Gao, Jinsheng
Abstract: In this study, the co-pyrolysis and co-liquefaction properties of corn straw (CS) and Shengli lignite (SL) were investigated. Individual liquefaction and co-liquefaction of CS and SL were performed and the characterization of co-liquefaction products was tested. The synergetic effect was discussed. The pyrolysis of SL can be obviously promoted by addition of CS, resulting in the larger weight loss of their blends compared to calculated values of their individual pyrolysis. The individual liquefactions of CS and SL show that CS gives much higher liquefaction conversion than SL at the same liquefaction conditions. During the co-liquefaction of CS and SL, there exists an obviously synergistic effect, which may be attributed to that free radicals or intermediates produced by thermally degradation of CS at low temperature aid the depolymerization of SL, and that the new-formed free radicals or intermediates from co-liquefaction can be easily decomposed and hydrogenated. The characterization of asphaltene and preasphaltene shows that the heteroatom-contained structure in asphaltene and the aliphatic structures in preasphaltene prefer to convert into lighter product compared to individual liquefaction of CS and SL. The largest enhancements in conversion of 8.67% and oil yield of 6.46% were obtained at 4/6 and 6/4 blend ratio of CS/SL among different blends, respectively, with 375 °C temperature, 30 min reaction time and 4 MPa initial pressure. Highlights: The pyrolysis of Shengli lignite is promoted by addition of corn straw. There exists synergistic effect in the co-liquefaction of corn straw and Shengli lignite. This synergism effect is concerned with the new-formed free radicals or intermediates from co-liquefaction.